BUILD PUBLIC TRUST THROUGH EXCELLENT SERVICE IN SCHOOL - M Yunus Abu Bakar; Hasan Baharun; Maulidatul Hasanah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to understand the implementation of excellent service in increasing public trust at SMA Nurul Jadid, Paiton, Probolinggo. This research uses a qualitative case study approach. The data collection technique is done through observation, interviews, and documentation. The data analysis technique was carried out through data reduction, data exposure, and concluding. The results showed that excellent service at SMA Nurul Jadid was implemented to increase public trust through; tangible modality, creating good communication, in-service training, the interconnection between employees, and an integrated approach to quality service. This research has implications for the importance of excellent service for every educational institution to ensure the loyalty of madrasa residents both internally and externally.